2018
DOI: 10.1002/acn3.630
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and probable rapid eye movement sleep behavior disorder

Abstract: ObjectiveTo systematically examine the association between alcohol intake and likelihood of having probable rapid eye movement sleep behavior disorder (pRBD) 6 years later.MethodsThe study included 11,905 participants (mean age: 47.7 years) of the Kailuan Study, free of stroke, cancer, Parkinson disease, dementia, and head injury in 2006. We determined pRBD using a validated RBD questionnaire–Hong Kong in 2012. Amounts and types of alcohol intake were collected with questionnaire. Participants were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The analysis was based on a subset of a Chinese cohort, the Kailuan Study, being conducted in the Kailuan community in Tangshan city, China (13) . In the Kailuan Study, 101 510 participants (81 110 men and 20 400 women) from the ages of 18-97 were recruited in 2006-2007 at eleven hospitals (study sites) (13)(14)(15) . These hospitals provide primary care for all participants of the Kailuan Study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was based on a subset of a Chinese cohort, the Kailuan Study, being conducted in the Kailuan community in Tangshan city, China (13) . In the Kailuan Study, 101 510 participants (81 110 men and 20 400 women) from the ages of 18-97 were recruited in 2006-2007 at eleven hospitals (study sites) (13)(14)(15) . These hospitals provide primary care for all participants of the Kailuan Study.…”
Section: Participantsmentioning
confidence: 99%
“…In 2012, information on sleep habits was collected in 12 990 participants (10 725 men and 2265 women) who had completed the survey in the Kailuan Hospital (the largest study site of the Kailuan Study) and were free of neurodegenerative diseases, as detailed previously (13,14) . We excluded participants with CVD, cancer and head injury (n 987) and participants who had incomplete sleep and alcohol intake information (n 98), leaving 11 905 participants (9776 men and 2129 women) in the current analysis.…”
Section: Participantsmentioning
confidence: 99%
“…Similarly, it was reported in America as Commercial drivers suffer from excessive daytime sleepiness due to age, body mass index and alcohol consumptions (16). Alcohol-impaired driving accidents due to sleepiness also contribute to approximately 31% and 34.1% of all traffic fatalities in the USA and china (17) respectively with common alcohol related crash reports in UK from similar cause (18). A prospective cohort study conducted in Japan showed the other predator for excessive daytime sleepiness to be cigarette smoking (19) (20) (21).…”
Section: Introductionmentioning
confidence: 76%
“…Downloaded from inhibitors and tricyclic antidepressants should be discontinued or avoided if possible. 5 Heavy alcohol use may also increase RBD episodes 6 and should be limited in individuals who have exhibited correlations between alcohol use and RBD episodes. Clonazepam and melatonin are most frequently used for symptomatic treatment of RBD, largely based on case series, and a smattering of other medications has also been reported to be effective.…”
Section: Symptomatic Treatments For Rbdmentioning
confidence: 99%